Physio Chemical Analysis of Different Municipal Canal of Muzaffurpur: Assessment of Physicochemical Parameters in the Municipal Canal of Muzaffarpur (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Analysis of the physicochemical parameters of the Municipal Canal Muzaffarpur was performed at various locations where canal water flows with pollution loads from highly commercial and industrial areas. Various physiochemical parameters were analysed during the investigation. The outcomes demonstrated that most of the physicochemical parameters of the Canal framework were inside or at the fringe contrasted with the ISI and WHO passable drinking water limit and may consequently be reasonable for homegrown purposes, yet because of serious atmosphere changes and expanded contamination, it requires noteworthy thought. The mean estimations of these parameters were contrasted and the standard qualities. For the different destinations, the turbidity was recorded over as far as possible. The estimations of the contemplated parameters at site 2 were higher contrasted with site 1 during the storm season and summer season.